2012
DOI: 10.5433/1679-0359.2012v33supl2p3143
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of proteolysis and sensory characteristics of prato cheese with adjunct culture

Abstract: Influence of adjunct cultures on the chemical and sensory characteristics, and proteolysis of Prato cheese was investigated. Cheeses were manufactured using a commercial starter culture and Lactobacillus strains (Lactobacillus plantarum or Lactobacillus helveticus) as adjunct cultures. Control cheeses lacked the adjunct culture. The chemical composition was analyzed at day 5 after manufacture and the proteolysis at days 5, 25, 45 and 65 of ripening. The sensory acceptance was assessed at 60 days. A split-plot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
(14 reference statements)
0
2
1
2
Order By: Relevance
“…Small peptides and free amino acids contribute to the sensory characteristics of Prato cheese [33]. Published data show that the use of L. helveticus as adjunct culture in Prato cheese significantly increased the levels of DPI [34] [35] [36]. There were no significant differences in DPI nor EIP between the CHN and CHN +LH cheeses in this research.…”
Section: Characterization Of Proteolysis During Ripeningcontrasting
confidence: 40%
See 1 more Smart Citation
“…Small peptides and free amino acids contribute to the sensory characteristics of Prato cheese [33]. Published data show that the use of L. helveticus as adjunct culture in Prato cheese significantly increased the levels of DPI [34] [35] [36]. There were no significant differences in DPI nor EIP between the CHN and CHN +LH cheeses in this research.…”
Section: Characterization Of Proteolysis During Ripeningcontrasting
confidence: 40%
“…Another study on Prato cheese, also with the addition of L. helveticus and L. plantarum, also reported acceptance improvements, with higher averages for the attributes flavor, texture and purchase intent in samples with the addition of L. helveticus [34].…”
Section: Sensory Analysismentioning
confidence: 92%
“…Other authors have observed that the addition of adjunct strains can improve flavor and other sensory attributes (de Souza et al, 2008). Sato et al (2012) found significant improvements in flavor and texture liking using a commercial starter culture combined with Lactobacillus strains (L. plantarum or L. helveticus) as adjunct cultures for the manufacture of Prato cheese. The authors attributed the differences in perceived flavor and texture to the higher levels of proteolysis oc- Figure 2.…”
Section: Consumer Testingmentioning
confidence: 99%
“…No queijo Prato a proteólise ocorre du rante a maturação e é o principal evento responsável pelas mudanças de textura, por meio da hidrólise da matriz proteica (SATO et al, 2012). Durante esse processo, as proteínas são hidrolisadas em várias outras estruturas, alterando sua forma original e com isso mudando as características reológicas do queijo (FANG et al, 2016).…”
Section: Fatiabilidadeunclassified